Pengembangan Sistem Informasi Monitoring dan Helpdesk Proyek Pengembangan Perangkat Lunak (Studi Kasus: PT Lua Kreatif Teknologi) - Alvin Naufal; Djoko Pramono; Bondan Sapta Prakoso (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2022)
Lua Kreatif Teknologi Inc. is a technology company that focuses on software development. Lua Inc. currently requires an independent project management information system that focuses on the needs of project monitoring and helpdesk, which runs during the project executing and monitoring & controlling phases and during after sales. Therefore, this study describes the development of a web-based information system based on the needs of Lua Inc. This information system development model applies the SDLC (Software Development Life Cycle) waterfall and uses UML (Unified Modeling Language) for its design. The results of the needs analysis for the development of this information system produce a context for using the system which has 47 functional requirements and 5 non-functional requirements. There are adjustments for running business processes (as-is) with those offered (to-be) through an information system that is built and modeled with BPMN (Business Process Modeling Notation). The system implementation process implements a single page application architecture that communicates between the client (React.js) and server (Node.js) using the HTTP protocol without any reloading on the client. The testing method uses black-box testing by conducting validation tests on the functional system and UAT (User Acceptance Testing) which will be tested on stakeholders at Lua Kreatif Teknologi Inc.